VD_FINDINFO Arrêt / 2016 / 557 vom 2. August 2017 - VD Tribunal cantonal (2017)
ÉVALUATION DE L'ATTEINTE À LA SANTÉ, RENTE D'INVALIDITÉ, NOUVELLE DEMANDE | 28 LAI, 4 LAI, 17 LPGA, 6 LPGA, 7 LPGA, 8 LPGA, 87 RAI